Learning to Love the World Anew: Vatican ii and Catholic Social Ethics - Mannion, Gerard (Toronto journal of theology, 2016)
This article explores how Catholic social ethics was developed and transformed since the late 1950s. It notes major shifts in perspective, method, and focus, thanks to John xxiii, before turning to examine how Vatican ii itself took this transformation further still, through the conciliar discussions and eventual key documents. It offers a summary and assessment of the most important conciliar documents in this respect. It then, in turn, explores the most significant developments in Catholic social ethics under each subsequent pontificate, focusing both on key teaching documents and on notable events, movements, and methods that emerged. In exploring the ebb and flow in Catholic social ethics in this period, the article particularly compares differing church-world dynamics evident in each period considered. Finally, it offers an overview and assessment of the transformative effect of Pope Francis's pontificate to date upon social ethics. In offering "joined-up" social ethics, Francis is not only helping to make the social vision of Vatican ii a major missionary priority for the church once again in interconnected and surprising ways, but is also offering genuinely groundbreaking contributions to the corpus of social thought and practice. As increasing numbers of Catholics find renewed inspiration in the socially transformative power of the gospel once more and find collaborators who share such values, the coming decades could prove to be among the most fruitful of all for the church's call to justice.